A comparative study: duration of screen time and sleep quality in university students and school children - Soe, May Khin Soe; Mohd Kamaruzihan, Nurul Qistina (2022)
Screen time has been found to affect sleep quality negatively. As there are many studies proving that poor sleep quality and excessive screen time is prevalent among school children and university students, a comparative study on both age groups is yet to be explored extensively so far. This study is focusing more on school-aged children and university students, as they are often associated with sleep deprivation.